The influence of internet celebrities on consumers' purchase intention and its educational significance - Hu, Jimin; Sidek, Shafie; Abd Rahman, Azmawani; Raja Yusof, Raja Nerina; Chen, Yanning (Auricle Global Society of Education and Research, 2023)
University students in China are increasingly embracing the use of celebrity endorsement in teaching. Celebrities are now able to rapidly and easily reach a huge audience because of the growth of social media platforms like WeChat, Weibo, and Douyin, which makes them an appealing marketing tool for educational institutions. The potential advantages of leveraging celebrity endorsements to advertise their programs and draw students have been acknowledged by educational institutions in China. In addition to examining educational celebrity endorsement and educational purchase intention attainment, the study examines students' desire to act as moderators and planned behavior theory in Chinese universities. 440 students from various Chinese universities participated in an online and in-person survey that collected the data for the analysis. According to the findings of structural equation modeling (SEM), teaching strategies have a positive impact on students' desires. The study's results also showed a connection between achieving educational purchase intentions and celebrity endorsement of educational products, student consumer choice, and student desire. Cross-sectional analysis, close-ended questions, and quantitative research are all used in the current study. In light of this, it is deemed crucial to use creative and engaging teaching strategies in the higher education sector. Educational institutions can create marketing plans that boost students' purchasing intentions and enrollment levels by focusing on attitudes, arbitrary standards, and perceived behavioral control. To demonstrate the relationships between the constructs under consideration, future research on this topic should involve longitudinal or field testing. There are major policy recommendations, calls for future research, and recommended theoretical and practical implications.